2015
DOI: 10.1159/000382032
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Clr Ligand Expression and NKR-P1 Receptor Function during Murine Cytomegalovirus Infection

Abstract: Viruses are known to induce pathological cellular states that render infected cells susceptible or resistant to immune recognition. Here, we characterize an MHC-I-independent natural killer (NK) cell recognition mechanism that involves modulation of inhibitory NKR-P1B:Clr-b receptor-ligand interactions in response to mouse cytomegalovirus (MCMV) infection. We demonstrate that mouse Clr-b expression on healthy cells is rapidly lost at the cell surface and transcript levels in a time- and dose-dependent manner u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…Previous studies have shown that infection of various mouse and rat cells with a number of viruses (MCMV, RC-MV-E, vaccinia, ectromelia) promotes a rapid loss of mouse Clr-b ( Clec2d ) and the rat Clr-b homolog rClr-11 ( Clec2d11 ) at both the steady-state transcript and cell surface levels [6,16,18,19] . To distinguish between infected and uninfected (bystander) cells at the single cell level, we infected mouse NIH3T3 fibroblasts over an early time course using a modified MCMV-GFP reporter virus in which an enhanced GFP transgene is driven by an immediate early gene (ie1/3) promoter in the MCMV-Smith (VR-194) strain [19][20][21] .…”
Section: Infection Reciprocally Modulates Clr-b Levels On Infectmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that infection of various mouse and rat cells with a number of viruses (MCMV, RC-MV-E, vaccinia, ectromelia) promotes a rapid loss of mouse Clr-b ( Clec2d ) and the rat Clr-b homolog rClr-11 ( Clec2d11 ) at both the steady-state transcript and cell surface levels [6,16,18,19] . To distinguish between infected and uninfected (bystander) cells at the single cell level, we infected mouse NIH3T3 fibroblasts over an early time course using a modified MCMV-GFP reporter virus in which an enhanced GFP transgene is driven by an immediate early gene (ie1/3) promoter in the MCMV-Smith (VR-194) strain [19][20][21] .…”
Section: Infection Reciprocally Modulates Clr-b Levels On Infectmentioning
confidence: 99%
“…To distinguish between infected and uninfected (bystander) cells at the single cell level, we infected mouse NIH3T3 fibroblasts over an early time course using a modified MCMV-GFP reporter virus in which an enhanced GFP transgene is driven by an immediate early gene (ie1/3) promoter in the MCMV-Smith (VR-194) strain [19][20][21] . While we consistently observed a loss of Clr-b surface expression on the infected population at later time points (GFP + , 12-24 h postinfection), at early time points the uninfected bystander population expressed elevated Clr-b surface levels relative to mock-infected parental cells (GFP -, 3-12 h postinfection; Fig.…”
Section: Infection Reciprocally Modulates Clr-b Levels On Infectmentioning
confidence: 99%
See 2 more Smart Citations
“…Its interaction with NKR-P1B inhibits NK cells and increases rat CMV virulence in rats (42). The MCMV genome also appears to encode for Clr-bindependent ligands, which can functionally engage NKR-P1B receptor in reporter cell assays (43). However, their identity, and whether they bear homology to Clr-b, remains to be determined.…”
mentioning
confidence: 99%